Cardiovascular Effects of Anabolic-Androgenic Steroids in Dietary Supplements - P. van der Bijl; P. van der Bijl (Jr) (National Electronic Information Consortium (NEICON), 2023)
Dietary supplements are regularly consumed by more than 70 % of the US population, as well as by competitive and non-competitive athletes. Anabolic-androgenic steroids (AAS) are frequently found in dietary supplements, and have the potential for multi-organ toxicity, including significant effects on the cardiovascular system. Cardiovascular toxicities of AAS include coronary artery effects, e.g. spasm, thrombosis and plaque rupture, leading to acute coronary syndromes and myocardial infarctions, as well as direct myocardial toxicity, causing left ventricular hypertrophy, fibrosis and dysfunction. Coronary and myocardial effects converge towards a common final pathway, causing heart failure, life-threatening arrhythmias and sudden cardiac death. The unregulated nature of AAS in dietary supplements has many ramifications. Both coaches and athletes should be aware that testing positive for a prohibited substance (including AAS) constitutes a potential doping violation. We advocate for improved education of the public at large regarding the potential for AAS to be included in dietary supplements, as well as its regulation by the appropriate authorities.